In vivo antitumoral effect of 4-nerolidylcatechol (4-NC) in NRAS-mutant human melanoma. (July 2020) - Alves-Fernandes, Débora Kristina; Oliveira, Érica Aparecida de; Hastreiter, Araceli Aparecida; Faião-Flores, Fernanda; Felipe-Silva, Aloisio Souza; Turato, Walter; Fock, Ricardo Ambrósio; Maria-Engler, Silvya Stuchi; Barros, Silvia Berlanga de Moraes
Abstract: NRAS-mutations arise in 15–20% of all melanomas and are associated with aggressive disease and poor prognosis. Besides, the treatment for NRAS-mutant melanoma are not very efficient and is currently limited to immune checkpoints inhibitors or aggressive chemotherapy. 4-nerolidylcathecol (4-NC), a natural product extracted from Pothomorphe umbellata, induces apoptosis in melanoma cells by ROS production, DNA damage and increased p53 expression, in addition to inhibiting invasion in reconstructed skin. Moreover, 4-NC showed cytotoxicity in BRAF/MEKi-resistant and naive melanoma cells by Endoplasmic Reticulum (ER) stress induction in vitro . We evaluated the in vivo efficacy and the systemic toxicity of 4-NC in a NRAS-mutant melanoma model. 4-NC was able to significantly suppress tumor growth 4-fold compared to controls. Cleaved PARP and p53 expression were increased indicating cell death. As a proof of concept, MMP-2 and MMP-14 gene expression were decreased, demonstrating a possible role of 4-NC in melanoma invasion inhibition. Toxicological analysis indicated minor changes in the liver and bone marrow, but this toxicity was very mild when compared to other proteasome inhibitors and ER stress inductors already described. Our data indicate that 4-NC can counteract melanoma growth in vivo with minor adverse effects, suggesting further investigation as a potential NRAS-mutant melanoma treatment. Highlights: 4-NC has antitumor effect in xenograft model of a NRAS-mutant melanoma. 4-NC shows a mild systemic toxicity when compared to other available therapies. 4-NC decreases tumor size in vivo by cytotoxicity and MMP inhibition. 4-NC is a promising contributor to the therapeutic arsenal against melanoma.